Pastoral Kehadiran: Wujud Pengembalaan Umat Dalam Gereja Sinodalitas - Kristeno, Marianus Rago; X, Intansakti Pius (Publisher STPKat, 2024)
The church is a living community of believers gathered by Christ into a